HAKIKAT RELASI MURID DAN GURU PERSPEKTIF K.H. HASYIM ASY’ARI DALAM KITAB ADABUL ‘ALIM WAL MUTA’ALLIM - Mizan As Siddiqi; Muhamad Priyatna; Abdul Jabar Idharudin (Jurnal Manajemen Pendidikan, 2026)
Background: Islamic education views the teacher-student relationship as a spiritual-transcendental bond, a medium for the instilling of adab, and character formation. However, the digital era has triggered an acute moral crisis, marked by the commercialization of education that alters this connection into a mechanistic transaction, stripping away the essence of character education. Objective: This study aims to deeply explore K.H. Hasyim Asy'ari’s ethical thoughts in the book Adabul 'Alim wal Muta'allim and formulate an adaptive-contextual teacher-student relationship model to address modern morality challenges. Method: The method employed is descriptive qualitative through library research with a historical-philosophical approach and textual hermeneutics. Data analysis was conducted using qualitative content analysis. Results: The study identifies five main dimensions of the teacher-student relationship according to K.H. Hasyim Asy'ari: sincerity in teaching and learning, reverence for teachers, educator exemplary, the moral-spiritual responsibility of teachers, and attaining the blessing of knowledge through adab. The integration of jurisprudence-sufism and the lillah principle distinguishes this concept from secular Western theories which tend to be positivistic-rational. Conclusion: K.H. Hasyim Asy'ari’s thought provides a solid antithesis to contemporary degradation of adab. Its contextualization demands the formation of "digital adab", wherein virtual spaces must incorporate affective values, exemplary behavior, and spirituality, rather than merely serving as formal, value-barren data transfer.